Method development of phenolic acid profiling analysis as tert‐butyldimethylsilyl derivative by gas chromatography‐tandem mass spectrometry. (19th October 2021) - Kim, Youngbae; Seo, Chan; Lee, Hyeon‐Seong; Ji, Moongi; Oh, Songjin; Choi, Byeong‐Chan; Kim, Doo‐Young; Park, Kyung‐Wuk; Park, Junseong; Paik, Man‐Jeong
Abstract: An efficient gas chromatography‐tandem mass spectrometry‐based method using tert‐ butyldimethylsilyl derivative was developed for the simultaneous analysis of 10 phenolic acids. Under optimal conditions, linearity in the range of 2–100 ng/ml exhibited correlation coefficient ( r ) of ≥0.999. Repeatability showed low relative standard deviation of <16.7%, and accuracy (% relative error) varied from −9.8 to 3.4. New mass spectra data sets of 10 phenolic acids were constructed in multiple reaction monitoring mode. When applied to Orostachys japonica (Maxim.) A. Berger, the 10 phenolic acids of salicylic, 4‐hydroxybenzoic, vanillic, m ‐coumaric, syringic, p ‐coumaric, protocatechuic, ferulic, gallic, and caffeic acids were positively identified. We believe that the devised method will be found useful for profiling phenolic acids in various plant samples. Abstract : MRM chromatograms of phenolic acids by GC‐MS/MS (a) Standard and (b) Wa‐song. Rays: 1 = Salicylic acid, 2 = 4‐Hydroxybenzoic acid, 3 = Vanillic acid, 4 = m‐Coumaric acid, 5 = Syringic acid, 6 = p‐Coumaric acid, 7 = Protocatechouic acid, 8 = Ferulic acid, 9 = Gallic acid, 10 = Caffeic acid, IS = Naproxen.